ACCIDENT-PRONE AREA STUDY ON THE STREET CIAWI PUNCAK BOGOR - Primadi Candra Susanto; Ryan Firdiansyah Suryawan; Hartono Hartono; Budi Aji Purwoko (ABNUS Publisher, 2021)
The purpose of this research is to find out the location of the route that often occurs accidents in Puncak and to provide input to the local government, especially the Department of Transportation to guard the location to regulate traffic, Bogor is a strategic road that connects Cianjur and Bogor regencies, as well as a route that connects the tourism area. around Puncak, Bogor. The average effective lane width of Jalan Raya Puncak, Bogor is 4.2 meters, the capacity of Jalan Raya Ciawi-Puncak is 3565 pcu / hour. Supporting facilities for traffic activities are still lacking with a ratio of 7 signs per kilometer in both directions, 119 warning signs consisting of 16 prohibited signs, 24 directive signs, 5 command signs and as many warning signs. 74 pieces. The research method is descriptive quantitative research, is a literature study and uses primary and secondary data from related agencies. This research is supported by the spot speed (local speed) is the instantaneous velocity on a certain part of the road at a fairly short distance or at a certain point. Spot speed can be measured among others by directly using a radar meter (speed gun). The results of direct observations in the field show that road equipment facilities on the Raya Puncak Bogor road section, especially for road sign facilities, are still lacking.